Comprehensive performance analysis of flexible asynchronous AC link under various unbalanced grid voltage conditions. (November 2021) - Imdadullah,; Amrr, Syed Muhammad; Iqbal, Atif; Asghar, M.S. Jamil
Abstract: A flexible asynchronous AC link (FASAL) system is a technology that interconnects two power system networks operating at the same or different frequencies. The FASAL system is a newly developed technology; therefore, it requires a thorough investigation under different unbalanced grid voltage conditions for better behavioral understanding and appropriate future controller design. In this paper, the FASAL system is analyzed under various symmetrical and asymmetrical unbalanced grid voltage conditions. Moreover, the performance of the back-to-back voltage source converter (VSC) based HVDC link is also analyzed to establish its comparison with the FASAL system under the same conditions. The FASAL and VSC-HVDC systems are modeled in PSCAD/EMTDC software environment. The simulation results illustrate that the FASAL system performance is better under transient as well as steady-state conditions. Furthermore, the reduction in power at the receiving end side is also lesser in the FASAL system. For example, a 10% sag contributes only a 15% dip in power in the FASAL system, whereas VSC-HVDC reports a 30% power dip for the same sag condition.